Moral dilemma: is there a moral difference between killing and letting die in healthcare? - Alanazi, Mansour M.; Alanazi, Mohammed R. (International Journal of Research in Medical Sciences, 2022)
The purpose of this paper was to prove that there was no moral difference between killing and letting one die in healthcare. It was important to be aware of the moral equivalence of killing and letting die. The Abrahamic religions; Islam, Christianity and Judaism, all argue for the sanctity of life. The world’s major religions Islam, Christianity and Judaism all have doctrines concerning the sanctity of life and they support the main arguments of this paper that there is no moral difference between killing and letting die. In relation to patient autonomy and the patient’s right to die, it is very important to highlight that doctors have a moral and legal responsibility to save lives. In addition, we discussed the distinction centres on the true definition of patient autonomy and who was responsible for defining the quality of life. The intention and foresight were critical points that supported the thesis statement that killing and letting one die were one in the same. The acts and omissions doctrine as described in this paper showed that there were no moral difference to kill a person or to let him die. Finally, we extensively discussed the various viewpoints regarding whether or not there was a moral difference between killing and letting die. There is no doubt that the debate over killing and letting die will continue for years to come. It is critical that the issue be addressed at this particular time in history with the advent of modern medical technology.